PSYCHOLOGICAL DETERMINANTS OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR: EXAMINING THE EFFECTS OF HARDINESS AND SELF-EFFICACY IN INDONESIA’S INTEGRATED COCONUT PROCESSING INDUSTRY - Dina Haya Sufya; Nur Alifah Sadillah (Universitas Muhammadiyah Lampung, 2026)
This study investigates the psychological determinants of Organizational Citizenship Behavior (OCB), focusing on the roles of hardiness and self-efficacy among employees in Indonesia's integrated coconut processing industry. Using a quantitative correlational design, the study involved 236 employees from a manufacturing company in Riau Province, Indonesia. Data were collected through adapted measures of hardiness, self-efficacy, and OCB. The data were analyzed using descriptive statistics, Pearson’s correlation to examine the bivariate relationships among variables, and multiple linear regression to test the simultaneous and partial predictive effects of hardiness and self-efficacy on OCB after normality, linearity, multicollinearity, and heteroscedasticity assumptions were examined. The results showed that both hardiness and self-efficacy were significantly and positively associated with OCB, with hardiness emerging as the stronger predictor. Together, these variables explained 27.8% of the variance in citizenship behavior. These context-specific findings from the Indonesian coconut processing sector highlight the importance of psychological factors in fostering cooperative behaviors. Practically, the findings suggest that human resource development and management can strengthen OCB through structured resilience training, supervisor coaching, mentoring programs, mastery-based work assignments, and constructive feedback systems that build employees' hardiness and self-efficacy.